(untitled) (Innovaciones Educativas, 2023)
The purpose of this essay is to explain the importance of Bloom’s revised taxonomy in the writing of learning outcomes, for which recommendations for its use are proposed. The document mentions the need to generate educational proposals that are more closely linked to the social context, which is why policies have been issued to promote the design and implementation of student-centered curricula. In this sense, the work developed by authors such as Kennedy (2006) and Biggs and Tang (2011) for the writing of learning outcomes is addressed. Finally, it is developed with an example, the coherence that should exist between learning outcomes, assessment and implementation of teaching-learning strategies, in the formative process of the student population, understood as constructive alignment. It is concluded that although taxonomies are a guide that proposes a hierarchical classification of the levels of development of cognitive and knowledge processes, their use should go from being a mechanical task to a process of reflection on the object of study of an academic discipline. Also, on the importance of carrying out the process of designing the results in work teams, with training on their elaboration and the use of taxonomies, for which the participation and accompaniment of experts in curricular matters becomes an essential requirement.